Climate information services in Africa: Experience from AICCRA Project in Senegal - Worou, Nadine (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This document is a presentation on climate information services in Africa: Experience of the AICCRA project in Senegal. It provides a summary of the AICCRA Senegal project, its intended impacts, the services provided and the decision support tools such as iSTA and Agdatahub developed within the AICCRA framework.